Fluglärmschutzkonzept der sogenannten Synopse auf dem Prüfstand neuerer Erkenntnisse der Lärmwirkungsforschung sowie gesetzlicher Rahmenbedingungen. Teil 1. - Scheuch, Klaus; Spreng, Manfred; Jansen, Gerd (Springer-VDI-Verl., 2007)
Kriterien für ein Schutzkonzept bei Fluglärmbelastungen in der Umgebung von Flughäfen wurden 2002 in der Zeitschrift für Lärmbekämpfung vorgestellt. Sie sind als "Synopse" zur Beurteilung von Fluglärmwirkungen bekannt und praktisch angewandt worden. Im Beitrag wird das Schutzkonzept der Synopse überprüft, da neue Veröffentlichungen auf experimenteller und epidemiologischer Grundlage entstanden sind, die sich z. T. auch mit der Synopse kritisch auseinandersetzen. Darüber hinaus ist das neue Fluglärmschutzgesetzes verabschiedet worden. In der Lärmwirkungsforschung zeigt sich insgesamt eine Verbesserung der Datenlage, ein Zugewinn an Erkenntnissen, aber auch eine weitgehende Übereinstimmung mit den Grundannahmen in der Synopse. Insbesondere die wesentlichen Bewertungsgrenzen und vorgeschlagenen präventiven Richtwerte für die einzelnen Schutzziele bedürfen keiner grundlegenden Korrektur, lediglich Ergänzungen und Präzisierungen. difu

Criteria for a protection concept against aircraft noise were published by Griefahn et al. in "Zeitschrift für Lärmbekämpfung" 2002 and became known as "synopsis". Since that time the synopsis was applied to practical situations in several cases. With this publication we reevaluate and check the given criteria and protection concepts of the synopsis. Since between 2002 up to 2007 a considerable number of new scripts and documentations concerning aircraft noise effects have been published. Some of the publications dealt critically with the synopsis. Meantime the German Federal Parliament has passed a new "Anti-Aircraft Noise Law". Concerning the Noise Effects Research on human beings there could be observed an overall better data basis, a considerable increase of knowledge, but also a wide approval to the basic statements of the synopsis. Especially the main limit values and recommended standard values concerning the singular protection targets are in no need of essential corrections. With this publication it is intended to give additions and precisitions. The evaluation of the effects of aircraft noise during the night has become reliable by the intensive "sleep - study" of the DLR. Physiological basis of the preventive standard by the synopsis is the so called "Cortisol -Model". On the other hand the awakening reaction of DLR is based on EEG measurements. The allowed numbers of maximum noise levels as NAT-criteria of the synopsis is lying below those of the DLR. The protection concept of the DLR is described by several preventive assumptions which are leading to an overestimate of 12 dB (A) regarding the realistic situation. This might be useful in some special cases. The criteria of the synopsis, on the contrary, are based on multiple additional health parameters and are more applicable to airports. Finally, the guidelines of the synopsis are compared with the limits of the new German Anti-Aircraft Noise Law as well as with the levels of some common noises as they daily occur.
Probation of the aircraft noise protective goals published in the so called "Synopse" with respect to latest findings of noise effects and legal provisions.
Keywords: Umweltschutz; Gesundheitsschutz; Lärm; Lärmschutz; Fluglärm; Fluglärmgesetz; Bewertung; Messung; Grenzwert; Lärmbelästigung; Flughafen; Flugplatz; Immissionsschutzrecht; Flugverkehr; Eckwert; Schlaf; Lärmwirkung; Schutzziel